2022
DOI: 10.1007/s10664-022-10227-1
|View full text |Cite
|
Sign up to set email alerts
|

Static test flakiness prediction: How Far Can We Go?

Abstract: Test flakiness is a phenomenon occurring when a test case is non-deterministic and exhibits both a passing and failing behavior when run against the same code. Over the last years, the problem has been closely investigated by researchers and practitioners, who all have shown its relevance in practice. The software engineering research community has been working toward defining approaches for detecting and addressing test flakiness. Despite being quite accurate, most of these approaches rely on expensive dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 88 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…Second, the rationale for using this dataset came from previous observations made by Pontillo et al. ( 2021 , 2022 ). In their study, the authors ran a state-of-the-art test smell detector named VITRuM (Pecorelli et al.…”
Section: Dataset Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the rationale for using this dataset came from previous observations made by Pontillo et al. ( 2021 , 2022 ). In their study, the authors ran a state-of-the-art test smell detector named VITRuM (Pecorelli et al.…”
Section: Dataset Constructionmentioning
confidence: 99%
“…These projects were highly diverse in terms of scopes and sizes, hence representing an ideal source to mitigate possible threats to external validity-our online appendix provides detailed statistics on those projects (Pontillo et al 2023). Second, the rationale for using this dataset came from previous observations made by Pontillo et al (2021Pontillo et al ( , 2022. In their study, the authors ran a state-of-the-art test smell detector named VITRuM (Pecorelli et al 2020) and identified a high number of test smells, i.e., they found that around 80% of test cases were smelly.…”
Section: Projects Selectionmentioning
confidence: 99%